2006
DOI: 10.1016/j.ibmb.2006.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of insect juvenile hormone biosynthesis☆

Abstract: The biosynthesis of insect juvenile hormone (JH) and its neuroendocrine control are attractive targets for chemical control of insect pests and vectors of disease. To facilitate the molecular study of JH biosynthesis, we analyzed ESTs from the glands producing JH, the corpora allata (CA) in the cockroach Diploptera punctata, an insect long used as a physiological model species and compared them with ESTs from the CA of the mosquitoes Aedes aegypti and Anopheles albimanus. The predicted genes were analyzed acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 45 publications
1
62
0
1
Order By: Relevance
“…Sequencing of an A. aegypti CA ϩ CC (corpora cardiaca) cDNA library revealed one EST encoding a full length ORF for a 245-amino acid short chain dehydrogenase that could be responsible for the oxidation of farnesol into farnesal (14). In addition, an EST encoding a segment of an ortholog of this gene was isolated from a CA ϩ CC cDNA library of the cockroach Diploptera punctata (GenBank acc: DV017939) (14). Screening the A. aegypti genome using this EST revealed an almost identical nonannotated sequence (AaSDR-1) and 4 additional sequences with a high degree of similarity (72-83%) (AaSDR-2 to AaSDR-5) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of an A. aegypti CA ϩ CC (corpora cardiaca) cDNA library revealed one EST encoding a full length ORF for a 245-amino acid short chain dehydrogenase that could be responsible for the oxidation of farnesol into farnesal (14). In addition, an EST encoding a segment of an ortholog of this gene was isolated from a CA ϩ CC cDNA library of the cockroach Diploptera punctata (GenBank acc: DV017939) (14). Screening the A. aegypti genome using this EST revealed an almost identical nonannotated sequence (AaSDR-1) and 4 additional sequences with a high degree of similarity (72-83%) (AaSDR-2 to AaSDR-5) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One EST was found in a CA library of A. aegypti encoding AaSDR-1 and its ortholog was also present in a CA library of the cockroach D. punctata (14). Short-chain dehydrogenases/reductases constitute a large family of NAD(P)(H)-dependent oxidoreductases, sharing sequence motifs and displaying similar mechanisms (16).…”
Section: Discussionmentioning
confidence: 99%
“…We first compared mRNA levels for these genes between wild-type and Mad mutant larvae at the 2nd instar using quantitative real-time PCR. Six enzymes, including JHAMT, farnesyl diphosphate synthase (FPPS), farnesol oxidase (FARox), farnesol dehydrogenase (FARD), cytochrome P450 6g2 (Cyp 6g2) and farnesoic acid O-methyltransferase (Famet), were chosen because they catalyze the key steps of JH biosynthesis and are predominantly expressed in the CA (Belles et al, 2005;Noriega et al, 2006). We found that in the Mad k00237 larvae, the mRNA levels of jhamt were decreased to less than half of that in wild type.…”
Section: Madmentioning
confidence: 99%
“…Bti is a gram-positive bacterium present in regular soil that can form endospores that produce the insecticidal Delta endotoxin, which is a toxic protein to the gut epithelium of mosquito larvae [8]. An additional agent is juvenile hormone, which can halt mosquito larval and pupal growth [9]. In foreign countries, there is a report that Bti can effectively reduce a number of mosquito larvae in a short period [10] and that juvenile hormone can efficiently eradicate Ae.…”
Section: Introductionmentioning
confidence: 99%